2015
DOI: 10.1186/s13071-015-1063-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-structural protein NS3/NS3a is required for propagation of bluetongue virus in Culicoides sonorensis

Abstract: BackgroundBluetongue virus (BTV) causes non-contagious haemorrhagic disease in ruminants and is transmitted by Culicoides spp. biting midges. BTV encodes four non-structural proteins of which NS3/NS3a is functional in virus release. NS3/NS3a is not essential for in vitro virus replication. However, deletion of NS3/NS3a leads to delayed virus release from mammalian cells and largely reduces virus release from insect cells. NS3/NS3a knockout BTV in sheep causes no viremia, but induces sterile immunity and is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…In addition, differences in tissue culture susceptibility observed between the three variants (and in comparison with BTV-25 and 26) raise questions pertaining to the nature of the viral genetic control(s) affecting transmission and susceptibility. Moreover, recent studies demonstrated that interactions between BT viral proteins are crucial in terms of tissue tropism and particularly in insect cells (Feenstra, Drolet, Boonstra, & van Rijn, 2015;Feenstra, van Gennip, Schreuder, & van Rijn, 2016;Nunes et al, 2014 andPullinger et al, 2016). Reverse genetics using mono-reassortants of BTV-26 genes in a BTV-1 background has been able to provide answers for some of these (Pullinger et al, 2016).…”
Section: Rt-qpcr Resultsmentioning
confidence: 99%
“…In addition, differences in tissue culture susceptibility observed between the three variants (and in comparison with BTV-25 and 26) raise questions pertaining to the nature of the viral genetic control(s) affecting transmission and susceptibility. Moreover, recent studies demonstrated that interactions between BT viral proteins are crucial in terms of tissue tropism and particularly in insect cells (Feenstra, Drolet, Boonstra, & van Rijn, 2015;Feenstra, van Gennip, Schreuder, & van Rijn, 2016;Nunes et al, 2014 andPullinger et al, 2016). Reverse genetics using mono-reassortants of BTV-26 genes in a BTV-1 background has been able to provide answers for some of these (Pullinger et al, 2016).…”
Section: Rt-qpcr Resultsmentioning
confidence: 99%
“…Current live attenuated BTV vaccines that are used in the field are not completely safe as some are linked with undesirable secondary reactions, such as teratogenic effects, reversion to virulence, and the risks of transmission to vectors. Vaccine studies with these DISA vaccines showed protection in vaccinated animals and inability to replicate in the Culicoides vector (25). The vaccine candidates that we are presenting in this report do not replicate either in cell culture or in the susceptible hosts and in that respect are more similar to an inactivated vaccine, but with several advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, both are important for virus replication in vitro. Previously, it has been shown that NS3/NS3a is required for viraemia in sheep and virus propagation in Culicoides (Feenstra et al, 2014a(Feenstra et al, , 2015. Thus, NS3/NS3a is crucial in vivo for virus transmission between the insect vector and the ruminant host.…”
Section: Discussionmentioning
confidence: 99%
“…NS3/ NS3a is not essential for virus replication in vitro, although NS3/NS3a knockout BTV showed a disturbed release in mainly insect cells (van Gennip et al, 2014). However, NS3/NS3a is essential for viraemia in the mammalian host as well as for virus propagation in Culicoides vectors in vivo (Feenstra et al, 2014a(Feenstra et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%